2009
DOI: 10.5194/angeo-27-1407-2009
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation of eddy-diffusion coefficients in the turbulent plasma sheet during substorms

Abstract: Abstract. Study of the plasma turbulence in the central plasma sheet was performed using the Interball-Tail satellite data. Fluctuations of the plasma bulk velocity in the plasma sheet were deduced from the measurements taken by the Corall instrument for different levels of geomagnetic activity and different locations inside the plasma sheet. The events that satisfied the following criteria were selected for analysis: number density 0.1-10 cm −3 , ion temperature T ≥0.3 keV, and average bulk velocity ≤100 km/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 16 publications
7
29
0
Order By: Relevance
“…This assumption predicts an eddy-diffusion coefficient in the Z direction of the order of 10 5 km 2 /s, to reproduce the observed plasma sheet thickness. This value agrees with the estimated eddy-diffusion coefficients obtained from measurements at ISEE-2, Interball/Tail, GEOTAIL and THEMIS satellites (Borovsky et al, 1997(Borovsky et al, , 1998Borovsky and Funsten, 2003a;Ovchinnikov et al, 2000;Troshichev et al, 2002; Stepanova et al, 2005Stepanova et al, , 2009. Recently, this theory has been verified in detail by , using Cluster satellite data and SuperDarn data.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…This assumption predicts an eddy-diffusion coefficient in the Z direction of the order of 10 5 km 2 /s, to reproduce the observed plasma sheet thickness. This value agrees with the estimated eddy-diffusion coefficients obtained from measurements at ISEE-2, Interball/Tail, GEOTAIL and THEMIS satellites (Borovsky et al, 1997(Borovsky et al, , 1998Borovsky and Funsten, 2003a;Ovchinnikov et al, 2000;Troshichev et al, 2002; Stepanova et al, 2005Stepanova et al, , 2009. Recently, this theory has been verified in detail by , using Cluster satellite data and SuperDarn data.…”
Section: Introductionsupporting
confidence: 83%
“…It was also found that the level of these fluctuations correlates with solar activity. Ovchinnikov et al (2000) and Stepanova et al (2005Stepanova et al ( , 2009 analyzed the relationship between the eddy-diffusion coefficient in the plasma sheet and the phase of isolated geomagnetic substorms using Interball/Tail and THEMIS satellite data. It was shown that the values of the eddy-diffusion coefficient increase significantly during the growth and expansion phases, being more pronounced in the later.…”
Section: Introductionmentioning
confidence: 99%
“…A clear manifestation of the existence of low‐frequency magnetospheric turbulence was also obtained through analysis of fluctuations of geomagnetic indices [see Takalo et al , 1993; Consolini and De Michelis , 1998; Uritsky and Pudovkin , 1998; Hnat et al , 2002; Stepanova et al , 2003b, 2005a; Pulkkinen et al , 2006; Wanliss and Uritsky , 2010], auroral absorption [ Stepanova et al , 2005b, 2006], and Polar UVI images [ Uritsky et al , 2008]. Measurements of the particle fluxes inside the plasma sheet allowed to study the fluctuations in the plasma bulk velocity and show that these fluctuations exceed significantly their average values [see Baumjohann et al , 1990; Angelopoulos et al , 1992, 1993, 1996, 1999; Borovsky et al , 1997, 1998; Borovsky and Funsten , 2003a, 2003b; Borovsky and Gary , 2009; Ovchinnikov et al , 2000; Troshichev et al , 2002; Stepanova et al , 2005c, 2009]. Despite differences in time resolution, the behavior of different components of the bulk velocity fluctuations is very similar, except for the bursty bulk flow events (BBFs), which produce asymmetry in the probability density function of the X and Y components of the inner plasma sheet flows in the GSE/GSM coordinate system.…”
Section: Introductionmentioning
confidence: 99%
“…E+[VB]=0 only if  and it is possible to neglect by electron pressure gradient and Hall term. The Reynolds number in the case of Coulomb collisions in the magnetosheath is extremely high (2.510 10 in accordance with (Borovsky & Gary, 2009) The violation of the frozen-in field condition is typical for the plasma sheet of the Earth (see, for example, Borovsky & Bonnell (2001), Troshichev et al (2002), Stepanova et al (2009Stepanova et al ( , 2011). Phan et al (1994) considered the obtained using AMPTE/IRM results as an evidence for violation of the frozen-in field condition in the magnetosheath as well.…”
Section: On the Applicability Of The Frozen In Condition To The Procementioning
confidence: 85%